The power frequency voltage divider calibration device and its uncertainty - Dongdong Xu; Weiwei Zhang; Nan Wang; Guangtao Wang; Guangke Xu (Energy Reports, 2020)
The power frequency high voltage divider is widely used to measure the power frequency high voltage and it is an important measuring instrument for high voltage test. Whether it is accurate or not directly affects the insulation monitoring level of power equipment closely related to the safety of power production, and it is of vital importance for power enterprises to ensure the measurement accuracy of power frequency high-voltage divider. The newly implemented JJG496-2016 <Verification procedure for high-voltage power divider> recommended three measurement methods: difference comparison, equal power bridge method and voltage ratio method. At present, only some literatures have introduced the measurement method using voltage ratio method and the measurement uncertainty evaluation procedure. This paper introduces a calibration device and measuring method of power frequency high voltage divider using the difference comparison method, and gives the uncertainty of the ratio difference and phase difference of power frequency high voltage divider obtained under the standard test environment.
Keywords: 330; Calibration device; Difference comparison method; Error value; High voltage divider; Uncertainty